Following 3D paths by a manipulator - Mazur Alicja; Płaskonka Joanna; Kaczmarek Mirela (Archives of Control Sciences, 2015)
In the paper a description of a manipulator relative to a desired three-dimensional path was presented. The path is parameterized orthogonally to the Serret-Frenet frame which is moving along the curve. For the path two different time parameterizations were chosen. The control law for the RTR manipulator which ensures realization of the task was specified. Theoretical considerations were illustrated by simulation results.